Students' Challenges in Learning Listening: A Case in SMAN 2 Tanjungpinang - Melany Apriyanti; Rere Melvina; Chemilia Azra Putri; E. Nur Putri Wulandari; Pohan, Erwin (Universitas PGRI Adi Buana Surabaya, 2024)
This study examines the challenges faced by students at SMAN 2 Tanjungpinang in developing listening comprehension skills in English as a Foreign Language (EFL). Using a qualitative approach, data were collected through listening tests and interviews with 35 students. The results identified key challenges, including limited vocabulary, unfamiliar topics, grammar knowledge deficits, fast speech, accent variations, unclear pronunciation, lack of practice, and environmental noise. These difficulties hinder students' ability to understand spoken English effectively. The findings suggest that targeted interventions, such as vocabulary-building activities, exposure to diverse accents, and improved classroom environments, are needed to enhance listening skills. This study provides valuable insights for teachers and policymakers to improve listening instruction in similar educational contexts.